Avaliação da Política de Cooperação Sul-Sul na UNILAB: percepções da integração sob o olhar dos discentes estrangeiros dos campi do Ceará - Medeiros, Ailana Linhares de Sousa (2017)
n this work we evaluate the South-South Cooperation policy of the University of International Integration of Afro-Brazilian Lusophony (UNILAB), from an in-depth perspective (GUSSI, 2008; RODRIGUES, 2008). The assessment is based on the perception of foreign students, who are members of UNILAB. Our main goal is to analyze the South-South Cooperation in practice, within the institutional-academic context. As a methodological and qualitative approach we employ: bibliographic analysis, participant observation and interviews. We discuss the circumstances of the Foreign Brazilian Policy that launched the international educational cooperation, which is linked to such contexts of the foundation of UNILAB. They are the conceptual basis that provide the theoretical-ideological support. UNILAB is born out of the policy of expansion of higher education proposed in the Lula Government (2003-2010) within internalization and internationalization policy. Its main activities focus on the training of human resources that contribute to the integration of Brazil and the nations that make up the Community of Portuguese-speaking countries. From the speech of the individuals inserted in politics, we consider evaluative dimensions that allow us to observe the integration: the trajectory from survival to civil war to higher education; the (un)common Portuguese language; the (dis)knowledge about UNILAB, the city of Redenção, the personal formation and the past; the feeling of gratitude;being in a Brazilian university and, finally, the perceptions about an integration. I realized that, in conclusion, the educational cooperation proposed by Unilab based on South-South Cooperation represents a break of the North-South hegemonic ideology because, even though many adversities arise in the relationships between the students and the local community, the goal of qualify human resources to contribute in their countries of origin is achieved. Moreover, within the context of integration, there are experiences that form and complement life histories which compose the continuous construction of the unilabian institutional trajectory and they end up externalizing, in practice, how the integration in the cooperation happens.